2009
DOI: 10.1021/jf802823q
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Inclusion Complex Formation and Solid-State Characterization of the Natural Antioxidants α-Tocopherol and Quercetin

Abstract: Cyclodextrin (CD) complexation procedures are relatively simple processes, but these techniques often require very specific conditions for each individual guest molecule. Variations of the coprecipitation from aqueous solution technique were optimized for the CD complexation of the natural antioxidants alpha-tocopherol and quercetin. Solid inclusion complex products of alpha-tocopherol/beta-CD and quercetin/gamma-CD had molar ratios of 1.7:1, which were equivalent to 18.1% (w/w) alpha-tocopherol and 13.0% (w/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 46 publications
7
69
0
Order By: Relevance
“…HP-b-CD in the PAE-HP-b-CD complex destroyed the interaction of PAE molecules to form a crystalline structure). These DSC results confirmed that PAE was no longer present as a crystalline material and its HP-b-CD solid complexes were present in the amorphous state because an HP-b-CD molecule encapsulated each PAE molecule [28].…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…HP-b-CD in the PAE-HP-b-CD complex destroyed the interaction of PAE molecules to form a crystalline structure). These DSC results confirmed that PAE was no longer present as a crystalline material and its HP-b-CD solid complexes were present in the amorphous state because an HP-b-CD molecule encapsulated each PAE molecule [28].…”
Section: Resultssupporting
confidence: 56%
“…Figure 3a, b and c present the H-NMR spectra of PAE, HPb-CD and PAE-HP-b-CD complex, respectively. The proton resonances of HP-b-CD were assigned based on the relevant literature [25][26][27][28]: chemical shifts in the range 3.85-3.95 ppm were those of H3 and H8, those in the range 3.40-3.75 ppm were those of H2, H4 and H7, and those in the range 3.70-3.85 ppm were those of H5 and H6. The appearance of chemical shifts at 5.51, 6.65 and 7.84 ppm in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD complexation procedures are relatively simple processes, but these techniques often require very specific conditions for each individual guest molecule (Koontz, Marcy, O'Keefe, & Duncan, 2009). Variations of the techniques have been used to form CD complexes.…”
Section: Introductionmentioning
confidence: 99%
“…These tools have been shown to be efficient to provide information about the interactions between the guest and the CD hosts, at the molecular level (Koontz, Marcy, O'Keefe & Duncan, 2009). Although it is not yet a routine method, photoacoustic spectroscopy of solids (PAS) has been shown to be a valuable technique for spectroscopic investigation of solid and semisolid matter.…”
Section: Introductionmentioning
confidence: 99%
“…However, the procedure of encapsulation, as well as conditions necessary to achieve the complexation are different and unique for each and every guest molecule, i.e. bioactive compound to be encapsulated [54]. Usually, it is required to stir, sonicate or heat the mixture of CDs solution and bioactives in order for complexation to occur [55,56].…”
Section: Molecular Inclusionmentioning
confidence: 99%